Drug resistant tuberculosis treatment outcomes at an urban ambulatory TB Unit in the City of Johannesburg - Maitisa, Norah (My University, 2018)
Background: Treatment of Drug Resistant Tuberculosis has historically been centralised and this model of care has posed challenges in management of such patients. Prolonged time to treatment and potential risk for continued community and nosocomial transmissions, capacity at these sites and availability of human resources to treat the increasing numbers of DRTB patients has been among those challenges. WHO set out to improve all DRTB outcomes especially in countries where the burden is high. Decentralisation of DRTB care has shown to improve these outcomes in many settings. Objectives: The main aim of the study was to describe any Rifampicin-resistant TB treatment outcomes in an ambulatory care model and to assess predictors of unsuccessful outcomes. Survival times for unsuccessful treatment outcomes were also determined. A comparison of the treatment outcomes by HIV status was also assessed. Methods: A retrospective cohort review of 335 patients with any Rifampicin-resistant TB diagnosis between January 2010 and January 2014, at Charlotte Maxeke Johannesburg Academic hospital DR-TB focal point was conducted. Survival analysis was done for unsuccessful outcomes. Multivariable Cox regression models were used to determine predictors of mortality, default and overall unsuccessful outcomes. Differences in outcomes by HIV status were compared using Pearson’s chi-square Results: Of the 335 patients analysed, 14 (4.2%) patients were still on treatment, 64 (19.1%) were successfully treated [with 17 (5.1%) cured and 47 (14%) completed treatment]. Unsuccessful outcomes were seen in 122 (36.4%) of the patients [with 30 (9%) died and 92 (27.5%) defaulted]. The remaining 135 (40.3%) patients were transferred out. There were no treatment failures in this cohort. Median survival time for unsuccessful outcomes was 3.2 months (IQR:1.4 to 9.2). Median time to death and default were 4.6 months (IQR:0.9 to13.8) and 3 months (IQR:1.4 to 8.5) respectively. There was no statistical difference found in proportions of successful and unsuccessful outcomes between HIV co-infected and HIV negative patients. Overall predictors of unsuccessful outcomes were: confirmed RMR-TB (HR=8.5; 95% CI: 2.0-35.2; p=0.003) and unconfirmed Rifampicin-resistance diagnosed on GXP alone (HR=10.9; 95% CI: 2.6-44.8; p=0.001). There were no statistically significant predictors of mortality found in this study. Predictors of default were: confirmed RMR-TB (HR=15.9; 95% CI: 2.1-116.5; p=0.006) and unconfirmed Rifampicin-resistance diagnosed on GXP alone (HR=17.2; 95% CI: 2.4-125.3; p=0.01). For a subgroup of HIV co-infected patients, being initiated on ART had 90% less hazards of defaulting (HR=0.1; 95% CI: 0.05-0.2; p=0.000). Age category >40 years also had 60% less hazards of defaulting in the HIV co-infected patients. Patients co-infected with HIV had higher hazards of default if they were diagnosed as confirmed RMR-TB (HR=10.8; 95% CI: 1.4-84.1; p=0.023) and unconfirmed Rifampicin-resistance diagnosed on GXP alone (HR=10.6; 95% CI: 1.4-80.2; p=0.022). Not initiated on ART was a predictor of unsuccessful outcome among HIV co-infected patients (HR=7.6; 95% CI: 4.1-14.1; p=0.000). Conclusion: Overall treatment outcomes were poor, with a low success rate (19.1%) and a high defaulter rate (27.5%). Mortality was comparable with other studies. Predictors of unsuccessful outcomes were confirmed RMR-TB and Rifampicin-resistance diagnosis on GXP only. Being initiated on ART and age >40 years reduced odds of defaulting by 90% and 60% respectively among HIV co-infected patients. Key recommendations: The high defaulter rate within the first few months of treatment impacts negatively on the control of DRTB, hence efforts to improve this are needed. Addressing factors associated with defaulting is crucial in DRTB clinics to curb transmission of DRTB in the community. All patients diagnosed with a GXP need immediate confirmation by LPA and culture/DST. Key words: Rifampicin resistant TB, Drug Resistant TB Treatment outcomes, Ambulatory DRTB care, DRTB/HIV co-infection
A dissertation submitted in partial fulfillment of Master of Science in the field of Infectious Disease Epidemiology. June 2018.
Keywords: Tuberculosis, Multidrug-Resistant